(untitled) (Biological Sciences - PJSIR, 2001)
Studies were undertaken on the su l phu r sa mpl es from Batal area, Di st r i ct No kk u n d i (B a l u chi stan) and the waste materi al from Quetta Sulphu r Refi nery whi ch i ndi cate th e presen ce of sul ph u r contents f rom 1 7-50%. Chem ica l eva l u ation an d liberation studi es were carri ed out to determi n e th e processi n g param eters for the u pgra dati on or the su l ph u r sam pl es. The studi es reveal ed th at fai rl y h i gh- grade sul phur mi ght be recovered from these sam pl es.